PERAN GURU BIMBINGAN DAN KONSELING DALAM PENURUNAN PERILAKU BULLYING DENGAN PENDEKATAN PSIKOEDUKASI - Almizri, Wahyu (Institut Syekh Abdul Halim Hasan Binjai, 2022)
AbstractViolence that occurs in adolescents is a form of behavior that is often encounteredand the trend continues to increase. One of the violence that occurs in the schoolenvironment is bullying. Bullying is violent behavior that is perpetrated by someoneagainst a group of weak people repeatedly by taking advantage of an imbalance ofpower, which is done physically, verbally or psychologically. Guidance andcounseling teachers have a role in providing assistance to students so they can knowand accept themselves and can know and accept their environment positively anddynamically. And being able to make decisions. Directing and realizing oneselfeffectively and productively for the future. In cases of violence that occur, especiallybullying, of course this is an urgency for the counseling teacher to be able to reducethis behavior, one of which is with the psychoeducation group. This paper willprovide stages in the implementation of psychoeducation because this paper is aliterature review that comes from several references.Keywords: Guidance and Counseling, psychoeducation.